Zwei bemerkenswerte Heteropteren aus der Sierra Nevada (Spanien) (Heteroptera). - Wagner, Eduard (Contributions to Entomology = Beiträge zur Entomologie, 1957)
There are described the hitherto unknown female of Heterocordylus montanus Lindberg 1934, a species related to H. genistae Scopoli, mentioning differentiation characters, and the male of Pachytomella alutacea Puton 1874, which, was found to be macropterous corresponding to the males of the other species.